Software of Pre-School Educational Establishments: Conceptual Dimension - Nadiya Frolenkova (Pedagogical Discourse, 2012)
An attempt to ground and describe software of pre-school educational establishments from the position of the conceptual dimension is carried out in the article. Substantive provisions, principles, methods and functions of the educational programs, for pre-school education are exposed, and also the aspect of the educational program is specified.